The safety of lumacaftor and ivacaftor for the treatment of cystic fibrosis - Guevera, Maria Talamo (Expert Opin Drug Saf, 2017)
INTRODUCTION: Lumacaftor-ivacaftor is indicated for treatment of cystic fibrosis (CF) in patients homozygous for the Phe-508del cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations. In clinical trials, treated patients showed improved pulmonary function, reduced pulmonary exacerbations, and other benefits. This article reviews safety of this therapy. AREAS COVERED: Safety findings in ivacaftor, lumacaftor and combined therapy trials, and reported subsequently through post-approval evaluation, were accessed by PubMed and Google searches using key words “VX-770”, “ivacaftor”, “VX-809”, and “lumacaftor”. Transaminitis was seen in ivacaftor and combination trials. Non-congenital cataracts were seen in pre-clinical animal studies and in children taking ivacaftor and combined therapy. Dyspnea occurs in some patients taking lumacaftor and combined therapy and usually resolves without stopping treatment. Lumacaftor is a strong inducer of CYP3A while ivacaftor is a CYP3A sensitive substrate. Combination therapy can decrease systemic exposure of medications that are substrates of CYP3A, decreasing therapeutic effect. Co-administration of lumacaftor-ivacaftor with sensitive CYP3A substrates or CYP3A substrates with narrow therapeutic index is not recommended. EXPERT OPINION: Lumacaftor-ivacaftor therapy may be associated with ocular and hepatic side effects. Specific recommendations for monitoring are available. Dyspnea occurs, especially during initiation of treatment. Potential drug interactions should be evaluated in patients taking combination therapy. The risk benefit ratio of lumacaftor-ivacaftor favors therapy.